N-Heterocyclic carbene stabilized Ag–P nanoclusters. Issue 4 (21st November 2014) - Khalili Najafabadi, Bahareh; Corrigan, John F.
Abstract : The N-heterocyclic carbene (NHC) 1, 3-di-isopropylbenzimidazole-2-ylidene ( i Pr2 -bimy) is found to be an excellent ligand for the stabilization of silver–phosphorus polynuclear complexes. Abstract : The N-heterocyclic carbene (NHC) 1, 3-di-isopropylbenzimidazole-2-ylidene ( i Pr2 -bimy) is found to be an excellent ligand for the stabilization of silver–phosphorus polynuclear complexes. The straightforward preparation and characterization of the clusters [Ag12 (PSiMe3 )6 ( i Pr2 -bimy)6 ] (1 ) and [Ag26 P2 (PSiMe3 )10 ( i Pr2 -bimy)8 ] (2 ) are described, representing the first examples of such structurally characterized, higher nuclearity complexes obtained using this class of ligands.